INHIBICION EN EL GANGLIO SIMPATICO CERVICAL SUPERIOR - ALVAREZ BUYLLA, RAMON (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
An attempt to furnish statistical basis for a structural correlation of the pituitary-adrenocortical interrelationship Results are based on the study of 75 male albino rats of the Sprague-Dawley strain, unilaterally adrenalectomized
AN ESC NAC CIENC BIOL
Keywords: INHIBICION, GANGLIO, SIMPATICO, CERVICAL; CIENCIAS DE LA VIDA; FISIOLOGIA HUMANA; FISIOLOGIA MEDICA